Peningkatan Kualitas Pendidikan: Program Pendidikan Profesi Guru Prajabatan dalam Pemenuhan Kebutuhan Guru Profesional di Indonesia - Arifa, Fieka Nurul; Prayitno, Ujianto Singgih (Jurnal Aspirasi, 2019)
The quality of education of a nation is determined by the quality of educators. Teachers as implementers of education at the basic, secondary and early age levels must have competencies and qualifications that meet national education standards. The Pre-service Teacher Professional Education Programs is a breakthrough to prepare certified professional teacher candidates. Teacher's requirements for academic qualifications are at least bachelor and must also have an educator certificate obtained through a certification program. With the end of certification through Teacher Professional Education and Training Programs, the entire certification process is taken through Teacher Professional Education Programs. This study uses a qualitative approach with library research method to find out ways in which the Pre-service Teacher Professional Education Programs policy meet the needs of professional teachers in Indonesia. In the implementation of Pre-service Teacher Professional Education Programs, there are still some challenges, namely: (1) the quality of Educational Personnel Education Institution, (2) the qualifications of prospective students, and (3) distribution of graduates. There need to be improvements in terms of governance and regulation to improve the effectiveness of the Pre-service Teacher Professional Education Programs.AbtrakKualitas pendidikan suatu bangsa ditentukan oleh kualitas pendidik. Guru sebagai pelaksana pendidikan pada jenjang dasar, menengah dan usia dini harus memiliki kompetensi dan kualifikasi yang memenuhi standar nasional pendidikan. Program Pendidikan Profesi Guru Prajabatan merupakan terobosan untuk menyiapkan calon guru profesional yang telah tersertifikasi. Persyaratan kualifikasi akademik guru setidaknya S-1 dan harus memiliki sertifikat pendidik yang diperoleh melalui program sertifikasi. Dengan berakhirnya sertifikasi melalui Program Pendidikan dan Latihan Profesi Guru maka seluruh proses sertifikasi ditempuh melalui Pendidikan Profesi Guru. Kajian ini menggunakan pendekatan kualitatif dengan metode kepustakaan (library research) untuk mengetahui bagaimana kebijakan Pendidikan Profesi Guru Prajabatan dalam pemenuhan kebutuhan guru profesional di Indonesia. Dalam pelaksanaannya Pendidikan Profesi Guru Prajabatan masih terkendala: (1) kualitas Lembaga Pendidikan Tenaga Kependidikan, (2) kualifikasi calon peserta didik, dan (3) penyerapan lulusan. Perlu adanya perbaikan dari sisi tata kelola dan regulasi guna meningkatkan efektivitas penyelenggaraan Pendidikan Profesi Guru Prajabatan.